2008
DOI: 10.1097/inf.0b013e3181673c3c
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Severe Sepsis Not Clinically Apparent During the First Twenty-Four Hours of Hospitalization in Children With Cancer, Neutropenia, and Fever

Abstract: Age > or =12 years and admission or 24-hour values of CRP > or =90/100 mg/L and IL-8 > or =200/300 pg/mL are predictors of sepsis not clinically apparent during the first 24 hours of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 29 publications
5
45
1
5
Order By: Relevance
“…Other studies, however, have reported that CRP concentration was not useful in predicting bacteremia and complicated infections in cancer patients with FN [21,22]. Other biomarkers, including interleukin (IL)-6, IL-8, and procalcitonin, have been shown to be [18,[22][23][24]. Therefore, if these biomarkers are performed together with CRP, it would be more helpful to predict prognosis in FN episodes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies, however, have reported that CRP concentration was not useful in predicting bacteremia and complicated infections in cancer patients with FN [21,22]. Other biomarkers, including interleukin (IL)-6, IL-8, and procalcitonin, have been shown to be [18,[22][23][24]. Therefore, if these biomarkers are performed together with CRP, it would be more helpful to predict prognosis in FN episodes.…”
Section: Discussionmentioning
confidence: 90%
“…The predictive value of CRP concentration, however, remains unclear. Several studies have reported that CRP was a reliable predictor of severe sepsis [17][18][19][20] and correlated well with MASCC riskindex score [15]. Other studies, however, have reported that CRP concentration was not useful in predicting bacteremia and complicated infections in cancer patients with FN [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…This case illustrates that, by definition, risk-prediction rules are not perfect [9,18]. Since secondary deteriorations are well-known in children with FN [24,37,38], close follow-up is essential after step-down to outpatient management.…”
Section: Discussionmentioning
confidence: 93%
“…In our experience of over 936 episodes evaluated during 3 years, 25% of children admitted with a high-risk febrile neutropenia will develop sepsis and 100% of episodeassociated deaths will occur in children with diagnosis of sepsis [17 ]. Studies aimed to discriminate between children at high or low risk for sepsis are currently available [17 ,18].…”
Section: Risk For Sepsismentioning
confidence: 99%